Success and Challenge Reporting through BOS Fund Management - Anugerah Ab’du Rasyid; Nurasik Nurasik (Universitas Muhammadiyah Sidoarjo, 2024)
This study assesses the management of school operational assistance funds (BOS) at Pucang 4 Public Elementary School, Sidoarjo Regency, Indonesia, focusing on planning, utilization, reporting, and identifying supporting factors and obstacles according to the 2021 BOS Technical Guidelines. Through qualitative methods including observation, documentation, and interviews, the study reveals successful planning and utilization but challenges in timely reporting. Despite limited financial expertise among school staff, efforts were made to meet reporting criteria, albeit with delays. The findings emphasize the importance of effective communication and training in financial management to enhance reporting practices, and suggest addressing challenges such as delayed fund disbursement and insufficient guidance from education authorities to ensure transparent and accountable use of BOS funds, offering insights for policymakers and educational administrators to refine guidelines and support mechanisms. Highlights: 1. Efficient BOS fund planning and utilization.2. Reporting challenges despite efforts.3. Communication crucial for transparent financial management. Keywords: School Operational Assistance Funds, Management, Reporting, Challenges, Education Governance